The Trainee Handbook / A Guide for Counselling and Psychotherapy Trainees - Bor Robert; Watts Mary (Sage Publications, 1999)
This book gives a comprehensive overview and a supportive guide to the practical, technical and administrative issues faced by trainees on counselling, counselling psychology and psychotherapy courses. Introduction, Training Routes for Counsellors and Counselling Psychologists and Psychotherapists, Effective Essay Writing, How to Write a Client Case Study, How to Write a Client Case Study, How to Write a Process Report, Written Communication about Clients, The Clinical Placement in Mental Heath Training, Supervision, Getting the Most out of Personal Therapy, The First Session with a New Client: Five Stages, What Do I Do If? Questions Commonly asked by Trainees, Guidelines for Professional Practice, Psychopharmacology: A Primer, Planning and Conducting and Writing Up Research, A Trainee's Perspective, Preparing for a Job, Index.